Search for the proton decay mode p ->nu K+ in Soudan 2 - Allison, W; Alner, G; Ayres, D; Barr, G; Barrett, W; Bode, C; Border, P; Brooks, C; Cobb, J; Cotton, R; Courant, H; Demuth, D; et al. (1998)
We have searched for the proton decay mode p → ν K+ using the one-kiloton Soudan 2 high resolution calorimeter. Contained events obtained from a 3.56 kiloton-year fiducial exposure through June 1997 are examined for occurrence of a visible K+ track which decays at rest into μ+ ν or π+ π0. We found one candidate event consistent with background, yielding a limit, τ/B(p → ν K+) > 4.3 × 1031 years at 90% CL with no background subtraction. © 1998 Published by Elsevier Science B.V. All rights reserved.